Five years of poisons information on the internet: the UK experience of TOXBASE. Issue 8 (20th July 2006) - Bateman, D N; Good, A M
Abstract : Introduction: In 1999, the UK adopted a policy of using TOXBASE, an internet service available free to registered National Health Service (NHS) departments and professionals, as the first point of information on poisoning. This was the first use worldwide of the internet for provision of clinical advice at a national level. We report the impact on database usage and NPIS telephone call loads. Methods: Trends in the pattern of TOXBASE usage from 2000–2004 are reported by user category. Information on the monographs accessed most frequently was also extracted from the webserver and sorted by user category. The numbers of telephone calls to the National Poisons Information Service (NPIS) were extracted from NPIS annual reports. Results: Numbers of database logons increased 3.5 fold from 102 352 in 2000 to 368 079 in 2004, with a total of 789 295 accesses to product monographs in 2004. Registered users increased almost tenfold, with approximately half accessing the database at least once a year. Telephone calls to the NPIS dropped by over half. Total contacts with NPIS (web and telephone) increased 50%. Major users in 2004 were hospital emergency departments (60.5% of logons) and NHS public access helplines (NHS Direct and NHS24) (29.4%). Different user groups access different parts of the database. Emergency departments access printable fact sheets for about 10% of monographs they access. Conclusion: Provision of poisons information by the internet has been successful in reducing NPIS call loads. Provision of basic poisons information by this method appears to be acceptable to different professional groups, and to be effective in reducing telephone call loads and increasing service cost effectiveness.